Pengaruh Kompetensi Pendidik dan Fasilitas Belajar Terhadap Kesiapan Kerja Peserta Didik Pelatihan Komputer di LKP Alfabank Semarang (Lembaga Pengembangan Kinerja Dosen, 2025)
Globalization has significantly impacted various aspects of life, including education, which is now expected to produce competent human resources capable of adapting to rapid technological developments. However, the high unemployment rate—particularly among vocational high school (SMK) graduates in Indonesia indicates a gap between the education system and labor market demands. The issue of graduate employability has become increasingly crucial, requiring collaborative efforts from educators, educational facilities, and non-formal education institutions. Non-formal education plays a complementary role in equipping learners with practical skills essential for the workforce. One such institution is the Alfabank Training and Course Institute (LKP Alfabank) in Semarang, which offers training in information technology and foreign languages. LKP Alfabank contributes to enhancing learners’ employability by providing industry-relevant training. This study aims to examine the role of non-formal education in supporting students’ job readiness through a case study of LKP Alfabank. This research involved a sample of 30 respondents.